TURKEYS’ EFFORT THAT TO BE ‘SOFT POWER’ IN THE MIDDLE EAST: A READING OVER THE DOCUMENTARY OF THE RIVER FLOWING WESTWARD - Serpil AYDOS (Fırat University, 2019)
With the support of the Promotion Fund of the Prime Ministry and Turkish Radio and Television Corporation (TRT) produced by the Bahçeşehir University, the documentary of The River Flowing Westward (Batı’ya Doğru Akan Nehir) was screened for in 2011. Turkey’s effort that to be ‘soft power’ in the Middle East in recent years is one of the reasons to production of the documentary. Turkey’s this effort required to revised their policies and values and create a new perspective related with the region. The documentary of The River Flowing Westward is a project that exactly produced with this purpose. There is a narrative in the documentary which speak not only on behalf of the Turks, but also on behalf of eastern peoples in general, Middle Eastern peoples in particular. Due to establishment of the narrative over Mesopotamia and the Middle East, The River Flowing Westward is a project that easily be able to adopt by the region peoples. Historical information’s, assertions, thoughts which were given in the documentary are especially in support of Turkish foreign policy related with Middle East. In order to put forward this assertion, discourse analysis technique for analysis of the documentary was used. Turkey’s representation of self-positions in the region, its approach to the Middle East and the representation mode of the region, its relations over Islam with Muslim people of the regions, has been analyzed by signifying practices in the film. Discourses and displays in the film, beside textual features, were examined in the context of Turkey’s historical and current Middle East policies. To perform a more systematic analysis, the data were analyzed under the heading of “The Birthplace of Civilization: Anatolia and Mesopotamia”, “East-West Comparison”, “Islamic Tolerance and the Contributions of Islam to Science”, “Turkey as a Bridge Between East and West and AK Party Rule”.